PENGARUH INTERVENSI CLOSED KINETIC CHAIN TERHADAP PERUBAHAN KEMAMPUAN FUNGSIONAL PADA PASIEN DENGAN OSTEOARTHRITIS GENU - Ratu Karel Lina (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Introduction: Osteoarthritis or calcification of the knee joint (genu) is a chronic disease that affects the joints and bones around the genu joint. Symptoms and signs of genu osteoarthritis are joint pain, joint resistance, morning stiffness, crepitus, deformity, asymmetric joint swelling, signs of inflammation, changes in gait. As a result of complaints of pain, the patient will reduce his activity, so that in a long period of time it can cause rehabilitation problems such as impaired flexibility, stability, reduction in muscle mass, decreased local muscle endurance, such as hamstrings and quadriceps. Physiotherapists play a role in improving physical function, fitness, and physical health so that they can improve individual performance. Active motion training can be used to increase muscle strength and can improve balance, this will have an impact on increasing functional activity. Exercise therapy that can be used includes closed kinetic chains. The purpose of this study was to determine the effect of closed kinetic chain intervention on changes in functional ability in patients with osteoarthritis genu. Methods: This study used an experimental research design with a one group pretest- posttest approach. The sampling technique used in this study was the Lameshow formula. The research will be carried out for four weeks with a frequency of exercise twice a week. The statistical analysis used in this study was Wilcoxon. Result: Research and statistical tests showed changes in pain and increased functional ability with p value <0.05. Conclusion: There is an effect of giving closed kinetic chain intervention to increase functional ability in patients with osteoarthritis genu.